Estimating construction costs - Peurifoy, R. L. 1902- (McGraw-Hill, 1989)
Introduction; Cost of construction labor and equipment; Handling and transporting material; Earthwork and excavation; Highways and pavements; Piling and bracing; Concrete structures; Floor finishes; Floor systems..